2001
DOI: 10.1001/jama.285.12.1592
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte-Reduced Red Blood Cell Transfusions in Patients With Anemia and Human Immunodeficiency Virus Infection<SUBTITLE>The Viral Activation Transfusion Study: A Randomized Controlled Trial</SUBTITLE>

Abstract: We found no evidence of HIV, CMV, or cytokine activation following blood transfusion in patients with advanced HIV infection. Leukoreduction provided no clinical benefit in these patients. These data demonstrate the importance of conducting controlled studies of effects of leukoreduction in different patient populations, since smaller studies in other patient populations have suggested leukoreduction may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 83 publications
0
81
0
Order By: Relevance
“…On the contrary, there was a trend (p = 0.12) toward longer survival among the recipients of nonleukoreduced RBCs. Thus, the VATS results 16 are the opposite of the findings of van de Watering et al 12 In both studies, the intention-to-treat analysis found no deleterious16 or beneficial 12 effect attributable to the receipt of leukoreduced RBCs. However, observational regression analyses adjusting statistically for the effects of measured prognostic factors for survival showed a statistically significant (p < 0.05) survival detriment 16 or benefit 12 attributable to leukoreduction.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…On the contrary, there was a trend (p = 0.12) toward longer survival among the recipients of nonleukoreduced RBCs. Thus, the VATS results 16 are the opposite of the findings of van de Watering et al 12 In both studies, the intention-to-treat analysis found no deleterious16 or beneficial 12 effect attributable to the receipt of leukoreduced RBCs. However, observational regression analyses adjusting statistically for the effects of measured prognostic factors for survival showed a statistically significant (p < 0.05) survival detriment 16 or benefit 12 attributable to leukoreduction.…”
mentioning
confidence: 74%
“…16 It detected no benefit from leukoreduction on either the primary endpoint of overall survival or any of the secondary endpoints used in the study. On the contrary, there was a trend (p = 0.12) toward longer survival among the recipients of nonleukoreduced RBCs.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…blood which would not have contained many of the biologic response modifiers that accumulate in very high concentrations over the last three weeks of storage in PRBCs. [54][55][56] Despite showing no differences in viral reactivation, studies comparing older stored blood (22-42 days of storage) should be completed in a large randomized controlled trial to better understand the possible role of stored blood in promoting viral reactivation.…”
Section: Viral Reactivationmentioning
confidence: 99%
“…Antibodies to leucocytes received during transfusions can cause febrile reactions which can be prevented by removal of leucocytes from the blood product. On the other hand, beneficial effects such as better survival of allografts in kidney transplantation 9 and improved survival in patients with HIV who receive transfusions 10 are attributed to the allogeneic leucocytes. Over the past decade, several studies have examined the possibility of an increased risk of postoperative complications associated with perioperatively transfused leucocytes.…”
Section: Introductionmentioning
confidence: 99%